Manejo biológico de Meloidogyne javanica em hortaliças: aplicação de caldos fermentados enzimáticos oriundos de matrizes fúngicas - Heinz, Breno Bevilaqua (2018)
The biological management of nematodes stands out for its viability in reducing agrochemicals in agricultural systems in favor of the sustainability of the production chain and human health. With advances in the biochemistry and biology of microorganisms, it is possible to obtain products from biotechnological processes, some of them focused mainly on the enzymatic production for agricultural purposes. The objective of this study was to evaluate in vitro and in vivo the nematicidal effect of fungal enzymatic broths on the control of eggs and juveniles (J2) of Meloidogyne javanica in lettuce and tomato in initial development. To do so, 3 enzyme broths from Metarhizium anisopliae, Beauveria bassiana and Trichoderma harzianum were produced and filtered for biomass removal. The egg suspension and J2 were obtained by the modified Baermann sieve and funnel method, respectively. Next, 100 μl of egg or J2 suspensions were plated on Elisa plates. Subsequently, 100μL of the extracts were applied, volume formed by several proportions consortium of each species (0, 25, 50, 75, 100,%). The egg hatch inhibition test consisted of 17 treatments with 8 replicates and 3 incubation periods (24, 48 and 72 hours), during which the evaluations were performed. For the juvenile mortality index, four replications and incubation time of 8, 16, 24 hours were used. Among the evaluation periods, there was a significant difference between the treatments, by the Scott-Knott test (p ≤ 0.05), where all the broths presented higher rates of egg inhibition (66.67-87.04%) and mortality J2 (44.44-90.00%) relative to the control. In the present study, the best 3 treatments were selected: nematodes + sterile distilled water (control) (T1), nematodes + 75% B. bassiana + 25% M. anisopliae (T2), nematodes + 75% B bassiana + 25% T.harzianum (T3), nematodes + 100% B. bassiana (T4). For the evaluation of lettuce damage, 10 replications were used, where the Irene cultivar (highly susceptible) was implanted. Seven days after transplantation, the nematodes were inoculated, and therefore the enzyme broths were inoculated within 72 hours. The following parameters of commercial interest were evaluated at 25 days after inoculation: leaf number, fresh matter weight, fresh matter weight, leaf dry weight, final population of nematodes (eggs and juveniles) and egg hatching rate. As for the penetration test of juveniles in tomato, there were 6 replications, where the cultivar used for the study was Santa Clara (susceptible). Seven days after transplantation, the enzyme broths were inoculated and the nematode suspension 24 hours later. The evaluation of the penetration rate was made, 48 hours later, by the nematode staining method in roots. There was a significant difference between the treatments in relation to the control, by the Scott-Knott test (p ≤ 0.05), and T2, T3 and T4 obtained positive responses to the variables evaluated, but T4, in the plant-nematoid- extract, presented phytotoxic symptoms. Thus, the use of enzymatic broths appears as a viable, innovative and effective alternative for the control of eggs and juveniles of M. javanica.